GENDERIZING CONSEQUENCES OF FAMILY POLICIES IN POLAND IN 2010S: A SOCIOLOGICAL PERSPECTIVE - SUWADA, KATARZYNA (Society Register, 2021)
The aim of this paper is to analyze four reforms introduced in the Polish family system in the 2010s. The reforms were introduced as an answer to a problem of very low fertility rates, as well as instruments helping women in achieving their work-life balance. The reforms are analyzed here in terms of their (de)genderization effects on Polish mothers and fathers. The use of a genderization-degenderization axis shows that the gendered division of domestic and care work is not challenged by the reforms, but it is rather reinforced by them. It is also doubtful if the reforms will manage to reverse current demographic trends.